2013
DOI: 10.1371/journal.pone.0073804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of UGT94F2 and UGT86C4, Two Glycosyltransferases from Picrorhiza kurrooa: Comparative Structural Insight and Evaluation of Substrate Recognition

Abstract: Uridine diphosphate glycosyltransferases (UGTs) are pivotal in the process of glycosylation for decorating natural products with sugars. It is one of the versatile mechanisms in determining chemical complexity and diversity for the production of suite of pharmacologically active plant natural products. Picrorhiza kurrooa is a highly reputed medicinal herb known for its hepato-protective properties which are attributed to a novel group of iridoid glycosides known as picrosides. Although the plant is well studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Benth (Plantaginaceae) is a perennial herb endemic to the north western alpine Himalayas. Most of its pharmacological activities are attributed to the iridoid glycosides, known as picrosides (Stuppner and Wagner 1989;Bhat et al 2013). In this study, we report a novel endophyte, isolated from the rhizome of this plant, producing a combination of three important metabolites-menthol, phenyl ethyl alcohol and 3-hydroxypropionic acid.…”
Section: Introductionmentioning
confidence: 95%
“…Benth (Plantaginaceae) is a perennial herb endemic to the north western alpine Himalayas. Most of its pharmacological activities are attributed to the iridoid glycosides, known as picrosides (Stuppner and Wagner 1989;Bhat et al 2013). In this study, we report a novel endophyte, isolated from the rhizome of this plant, producing a combination of three important metabolites-menthol, phenyl ethyl alcohol and 3-hydroxypropionic acid.…”
Section: Introductionmentioning
confidence: 95%
“…The regulation pattern of squalene synthase, squalene epoxidase, cycloartenol synthase and WsCPR1 and WsCPR2 in leaves and roots at various developmental stages in relation to dynamics of withanolides accumulation, indicated towards their tissue-specific biosynthesis [ 22 ]. In our earlier findings, we have reported that exogenous application of methyl jasmonate (MeJA) and salicylic acid (SA) increases withanolide content due to the presence of stress regulatory elements within the upstream promoter regions of their genes [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, picrocrocin was found in N. benthamiana when 3-hydroxy-β-cyclocitral was provided by CCD2, indicating apocarotenoid UGT activity in tobacco (Diretto et al 2019). Although UGT86C4 (Bhat et al 2013),…”
Section: Identification Of Unprecendented C 13 -Apocarotenol Ugtsmentioning
confidence: 98%